Adsorption and catalytic performance of pipe growth rings from water distribution networks using 5-BSA as the target pollutant. (December 2021) - Huang, Wanyi; Yuan, Yixing; Zhong, Dan; Ma, Wencheng; Yuan, Yuan; Zhang, Peng
Abstract: In this study, we investigated the use of pipe growth rings from water distribution networks as a catalyst in heterogeneous Fenton-like oxidation processes. The major constituents of real pipe growth rings (α- and γ-FeOOH) were prepared and considered as a simulated growth ring (SGR). Its performance in removing 5-bromosalicylic acid (5-BSA), a novel phenolic halogenated disinfection byproduct, was examined. SGR exhibited strong catalytic ability and a certain degree of adsorption capacity. Under acidic conditions, the adsorption and oxidation efficiencies were 32.65% and 87.67%, respectively. Furthermore, 72.19% of 5-BSA could be oxidized even at pH0 of 7. Kinetic characterizations at various temperatures revealed that both the adsorption and catalytic oxidation processes followed pseudo-second-order kinetic models and were surface-controlled with high activation energies (31.26 and 23.58 kJ mol −1, respectively). Ecotoxicity analyses of the transformation products (TPs) showed that the SGR/H2 O2 system could effectively reduce the toxicity of 5-BSA. Moreover, the number of iron ions leaching from SGR was below 0.1 mg L −1 in all experiments. The results of this study support further investigation of using real pipe growth rings in off-line water treatment, as well water network contamination remediation. Graphical abstract: Image 1 Highlights: The simulated pipe growth ring was used as the adsorbent and catalyst. 87.67% of 5-BSA was removed by SGR/H2 O2 system. Pseudo-second-order models fitted the adsorption and oxidation kinetic data well. The adsorption and oxidation processes had high activation energies. The toxicity of 5-BSA and its transformation products was effectively reduced.